Mechanical properties of 3D printed polymers - Yahamed, Azem; Ikonomov, Pavel; Fleming, Paul D.; Pekarovicova, Alexandra; Gustafson, Peter; Alden, Arz Qwam; Alfrafeek, Saif (Journal of Print and Media Technology Research, 2023)
Polymeric bone implants are used in many medical applications. To create bone structures from plastics that can match the real bones, the structure and mechanical properties must be tested to make sure they can sustain loads comparable to the original. Also, it is very important to use proper materials that provide biocompatibility. In this work, the mechanical properties of 3D printed samples of thermoplastic materials that can be used for 3D printing of human bone structure substitutes were tested. The thermoplastics that were printed using 3D printing are acrylonitrile butadiene styrene (ABS), Digital ABS™, polylactic acid (PLA), polyetherimide ULTEM 9085 and polyamide PA 2200. The samples of ABS and PLA were printed using fused deposition modeling technology (FDM), Digital ABS™ was printed using PolyJet™ technology, and ULTEM 9085 and PA 2200 were printed using selective laser sintering (SLS). Compression tests showed that PLA and Digital ABS™ create anisotropic 3D printed structures, because they exhibited different stress vs. strain properties in different directions. The samples made from ABS, ULTEM9085 and PA2200 have the same shape of stress-strain curves in different printing directions, but different slopes, which shows that these printed structures are also anisotropic. Differential scanning calorimetry was used to acquire the thermal analysis profile of these polymers. The thermal analysis results of these polymers indicate that ABS and ULTEM9085 are amorphous while PLA is partially crystalline and PA2200 is completely crystalline.